Challenges of Domestic Tourism Development in Ethiopia: Stakeholders’ Perspective: Research article - Mersha Ademe, Alemneh; Tuffa Birru, Worku (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2024)
This study explores the challenges of domestic tourism development in Ethiopia from the standpoint of key stakeholders. A mixed-method design was used in the study. Quantitative data were gathered from 159 key tourism stakeholders, including government agencies, hotel and tourism service providers, industry associations, academics, and experts. Qualitative data were gathered from ten purposely selected key informants, including two from each of the following groups: government officials, high-level experts, academics, tour operators, and national guides. Descriptive statistics and exploratory factor analysis were used to analyze quantitative data, while descriptive content analysis was used to analyze qualitative data. The findings show that citizens' limited tour and travel culture, government strategic directions and priority issues, as well as capacity issues such as research gaps and a lack of proper institutional structure, are major challenges to the development of domestic tourism in Ethiopia. It is recommended that stakeholders strengthen their coordinated and collaborative efforts in developing sector-specific strategies, tactics, legislation, regulations, legal frameworks, and institutional structures.